Developing a framework for Swiss outpatient pediatric research network - Kuske, Chantal; Maione, Salvatore; Soldini, Emiliano; von Rhein, Michael (Frontiers in Pediatrics, 2025)
AimsIn Switzerland, availability of pediatric outpatient data for research is limited. Pilot projects showed the benefits of collaborative networks for research, but there is no common understanding on how to best organize, govern, operate and fund these. This project aimed at developing a framework for the establishment of a nationwide collaborative outpatient pediatric research network.MethodsFollowing a qualitative approach, we conducted individual interviews, a workshop and a focus group with pediatricians and other healthcare stakeholders to discuss various aspects related to the development of the research network, including motivations for participation, retention strategies, perceived barriers, expected challenges, and previous experiences.ResultsParticipants were interested and willing to join such a network and gave valuable inputs, but also emphasized important challenges, particularly time constraints/limited resources, data management/IT infrastructure and funding. These insights allowed developing the outline of a three-step iterative implementation plan.ConclusionsThe project emphasized key elements to consider for the development of a Swiss outpatient pediatric research network sustainable in the long term, that would mark a pivotal advancement for pediatric healthcare research.